Precision cancer therapy: profiting from tumor specific defects in the DNA damage tolerance system - Buoninfante, Olimpia Alessandra; Pilzecker, Bas; Aslam, Muhammad Assad; Zavrakidis, Ioannis; van der Wiel, Rianne; van de Ven, Marieke; van den Berk, Paul C M; Jacobs, Heinz (Oncotarget, 2018)
DNA damage tolerance (DDT) enables replication to continue in the presence of a damaged template and constitutes a key step in DNA interstrand crosslink repair. In this way DDT minimizes replication stress inflicted by a wide range of endogenous and exogenous agents, and provides a critical first line defense against alkylating and platinating chemotherapeutics. Effective DDT strongly depends on damage-induced, site-specific PCNA-ubiquitination at Lysine (K) 164 by the E2/E3 complex (RAD6/18). A survey of The Cancer Genome Atlas (TCGA) revealed a high frequency of tumors presents RAD6/RAD18 bi-allelic inactivating deletions. For instance, 11% of renal cell carcinoma and 5% of pancreatic tumors have inactivating -deletions and 7% of malignant peripheral nerve sheath tumors lack . To determine the potential benefit for tumor-specific DDT defects, we followed a genetic approach by establishing unique sets of DDT-proficient and -defective lymphoma and breast cancer cell lines. In the absence of exogenous DNA damage, tumors grew comparably to their controls and . However, DDT-defective lymphomas and breast cancers were compared to their DDT-proficient controls hypersensitive to the chemotherapeutic drug cisplatin (CsPt), both and CsPt strongly inhibited tumor growth and the overall survival of tumor bearing mice greatly improved in the DDT-defective condition. These insights open new therapeutic possibilities for precision cancer medicine with DNA damaging chemotherapeutics and optimize Next-Generation-Sequencing (NGS)-based cancer-diagnostics, -therapeutics, and -prognosis.